Statistical estimation of the infl uence of the factors of «technological leadership» on the dynamics of labor productivity in the subjects of the Russian Federation - S. A. Sychev (Статистика и экономика)
The purpose of this article is to analyze the influence of production factors on the dynamics of labor productivity at the level of the subjects of the Russian Federation. For the purposes of research as a complex indicator characterizing a wide range of socio-economic indicators affecting the productivity of labor, it is proposed to use composite indicators – “Securing the labor market with high-performance jobs.” In addition to the abovementioned quantitative characteristic of the labor market security with high-performance jobs, the material, technical and innovation-investment factors of the regional economy were analyzed as labor productivity factors. The infl uence of these factors on the dynamics of labor productivity was evaluated from two directions: increasing the level of manufacturability of the products and increasing the technology of the level of production and equipment of labor on the basis of the following indicators: the share of high-tech and knowledge-intensive industries in the gross regional product; Share of domestic expenditure on research and development in the gross regional product; Coeffi cient of depreciation of fi xed assets; Share of investments in fi xed assets in the gross regional product. Based on the results of the study, the nature of the relationship between the dynamics of labor productivity and the provision of the economy with high-performance jobs for different groups of regions of Russia was revealed. The relevant interaction between the processes of creating highproductivity jobs and their richness of the economy has been confi rmed, a description of the nature of this interaction has been carried out, groups of entities that have a typical and atypical impact from this indicator have been identified. Based on the results of the initial stage of the study, it was stated that it is necessary to conduct a more detailed analysis of the impact of the level of manufacturability and the science intensity of products, as well as the effect of labor payment on the dynamics of labor productivity by subjects of the Russian Federation. Conclusions and patterns of further analysis characterize the targeted direction of the dependence of the effective indicator and a group of indicators describing the material, technical and innovation-investment factors of the economic environment on certain groups of Russian regions.